Mechanical Characterization of AA7050-TiC Metal Matrix Composites under as Cast as condition. (2018) - Ranganathan, Aditya; Akshay Krishnan, P.V.; Nambiar, Akshay S.; Mohan Kumar, S.; Ravi Kumar, V.
Abstract: The present works describes the mechanical properties of AA 7050 metal matrix composites reinforced with TiC. TiC particles of size 325 mesh was taken as the reinforcement material to prepare the metal matrix composites using stir casting technique. The percentage of reinforcement varied from 0 to 6% wt in steps of 2%. Mechanical characterization, such as tensile strength, hardness test, density tests were conducted as per ASTM standards. Experiment results reveal that there is an improvement in Ultimate tensile strength and hardness properties with the increase in the percentage of reinforcement. Optical microscopy technique was used to examine microstructures of the sample specimens and the microstructure revealed uniform distribution of particles and presence of reinforcements in the matrix phase. Experimental studies invokes that the 6%wt of TiC increases the tensile strength by 9% and hardness values by 10% comparing with that of as cast AA7050. Results also evident that there was a decrease in ductility and percentage of elongation with the increase in the percentage reinforcement.